IMPLEMENTASI KONSEP GREEN ECONOMY TERHADAP PENGELOLAAN TAMAN WISATA ALAM WIRA GARDEN KOTA BANDAR LAMPUNG, SEBAGAI UPAYA MEWUJUDKAN PEMBANGUNAN EKONOMI YANG BERKELANJUTAN - Diogsha, Hr; Noviarita, Heni (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2024)
Lampung is one of the provinces in Indonesia which is famous for its beautiful tourism, one of which is the Wira Garden natural tourist park in Lampung province, Wira Garden is famous for its clear water. Gradually the number of visitors increases, so the volume of waste increases due to the lack of awareness of the public and visitors regarding waste management. well. For this reason, researchers are interested in researching case studies. The type of research taken is descriptive qualitative using a phenomenology approach and a case study approach. This research uses secondary data through literature reviews from various books, research journals and other literature related to research. aims to create descriptions, systematic, factual and accurate descriptions of the nature and relationships between the phenomena being investigated. Green Economy implementation activities with the 3R concept (Reduse, Reuse, Recycle). It is hoped that this activity can be an alternative in preserving the environment, especially tourism, to improve the economy and sustainable development